Antioxidantes na dieta de frangos de corte - Boschini, Carolina (2011)
This study aimed to investigate the effects of a product containing a combination of antioxidants (CA) and different levels of vitamin E on performance, carcass traits and meat quality of broilers. A total of 840 Cobb male broilers were fed experimental diets from 1 to 35 days. A completely randomized experimental design was used. Dietary treatments consisted of T1- 200ppm CA, T2- 200ppm CA + Vitamin E (20 ppm), T3- 200ppm CA + Vitamin E (40ppm), T4- 200ppm CA + vitamin E (60ppm), T5- 200ppm CA + vitamin E (80ppm), T6- vitamin E (80ppm). A basal corn-soybean meal diet was formulated according to requirements established by Cobb. Performance was not affected by dietary treatments. Carcass yield and cut-ups were not signifi-cantly influenced, but a numerical improvement of breast and thigh was observed in birds fed T3. Meat colorimetry was significantly affected, finding the best results to L* (T5), a* (T1 and T5) and b* (T6), but results did not differ from T2, T3, T4 and T5. A lowest TBARs index was observed in birds fed T5, indicating lower meat lipidic pe-roxidation. These results indicate that the CA with any level of vitamin E did not change the broiler performance and efficiency factor. The CA improved carcass yield and cut-ups, color and decreases meat lipid peroxidation.